Supramolecular Porphyrin Polymers in Solution and at the Solid−Liquid Interface - van Hameren, Richard; van Buul, Arend M; Castriciano, Maria A; Villari, Valentina; Micali, Norberto; Schön, Peter; Speller, Sylvia; Monsù Scolaro, Luigi; Rowan, Alan E; Elemans, Johannes A. A. W; Nolte, Roeland J. M (Nano letters, 2008)
We have investigated in detail the self-assembly of a chiral porphyrin trimer in different solvents and correlated this behavior to the aggregation of the molecule at a solid−liquid interface. In n-hexane and cyclohexane, CD spectroscopy and dynamic and static light scattering studies showed that the porphyrin trimer self-assembles already at micromolar concentrations into long, chiral supramolecular polymers, which precipitate as fibers when the solution is drop-cast onto a mica surface. In contrast, in chloroform, the compound is molecularly dissolved up to concentrations of 0.2 mM and when micromolar solutions are drop-cast onto mica, no precipitation of large assemblies occurs. Instead, at the moment that the chloroform film becomes subject to spinodal dewetting and the porphyrin trimers within this film start to self-assemble, extended patterns of equidistant lines of single molecule thick columnar stacks are formed.